Tree planting program - UiTM, UGC (UiTM Green Centre, 2025)
A tree planting program was held on 24 April 2025 (thursday) at the main entrance field of UiTM Shah Alam, in conjunction with pes day: tree plantation drive. This program was jointly organized by the IEEE UiTM student branch, College of Engineering studies UiTM Shah Alam, and the UiTM Green Centre (UGC). The objective was to foster awareness of environmental sustainability among students and staff.